Optic nerve sheath diameter measurements monitor the impact of venous sinus stenosis and surgery on intracranial pressure in NF2 meningioma patients - Julian Zipfel; Mykola Gorbachuk; Florian Grimm; Ulrike Ernemann; Martin Ulrich Schuhmann; Marcos Tatagiba; Isabel Gugel (Scientific Reports)
Abstract The study aimed to evaluate intracranial pressure (ICP) in NF2-associated meningiomas using perioperative optic nerve sheath diameter (ONSD) measurements. We retrospectively analyzed bilateral ONSD in 48 NF2 patients with 90 operated intracranial meningiomas. The mean ONSD was calculated while considering factors like symptoms of increased ICP, tumor location, tumor-induced venous sinus stenosis, and Simpson grading. 403 ONSD measurements were performed over a mean follow-up of 68 ± 67 months before and 27 ± 35 months after surgery. Tumor locations included the skull base (49%), convexity (22%), falx (18%), tentorium (6%), orbit (3%), and the ventricle (2%). Significant findings included a decrease in ONSD from 6.11 ± 0.89 mm to 5.88 ± 0.91 mm postoperatively (p = 0.01), with further reduction at the last MRI (mean 5.76 ± 0.86 mm, p < 0.001). Higher preoperative ONSD was associated with venous sinus stenosis (p < 0.001) and increased ICP symptoms (p = 0.033). Postoperatively, there was a complete regression of symptoms in patients with preoperative increased ICP. Early and continual ONSD monitoring is crucial for NF2 patients with intracranial meningiomas, particularly those with venous sinus stenosis or increased ICP symptoms. Surgery that preserves the venous sinus while reducing tumor volume can lower intracranial pressure even in the long run.